Cord levels of zinc and copper in relation to maternal serum levels in different gestational ages - May Abdellatif; Ismail Mohamed Elhawary; Marwa Mohamed Mahmoud; Eman R. Youness; Walaa Alsharany Abuelhamd (SpringerOpen, 2021)
Abstract Background A few published data on maternal and cord levels of zinc and copper with conflicting results were reported. We aimed to measure zinc and copper levels in the maternal blood and cord blood of newborns and correlate their levels with the gestational age and anthropometric measurements. This cross-sectional study included 75 full-term and preterm neonates and their mothers. These neonates were divided into 2 groups according to their gestational age. Serum levels of copper and zinc were estimated for the mothers of the studied neonates as well as their cord samples. This was done using atomic absorption spectrophotometry. Results The mean cord serum zinc in full term was 0.88 ± 0.18 μg/ml whereas in preterms was 0.73 ± 0.13 μg/ml. The mean cord copper in full term was 1.37 ± 0.26 μg/ml, whereas in preterms was 0.75 ± 0.28 μg/ml. Comparison between cord zinc and copper levels and maternal levels were statistically significant (p < 0.001). A significant positive correlation was found between zinc levels in neonates and their mothers (r 0.644; p < 0.000) and a similar positive correlation was found between copper levels in neonates and their mothers (r 0.625; p 0.000). A highly significant positive correlation was found between cord zinc and copper and anthropometric measurements. Conclusion The present work draws our attention to the significant correlation between trace elements in pregnant mothers and fetal development. Also, prematurity adversely influences zinc and copper levels in neonates.